Memo for Max Bredig, January 27, 1941 (1941)
Dr. George Barksy, President of Barsky & Strauss Inc., laboratories of Murray Hill, New York City, would like Max Bredig (1902-1977) to phone him.
Keywords: Bredig, Max Albert, 1902-1977; Barksy, George